ALFABETIZACIÓN CINEMATOGRÁFICA EN LAS AULAS. ATURUXO FILMS - Lic. Sergio CLAVERO IBÁÑEZ DE GARAYO (Fonseca, Journal of Communication, 2023)
This article tackles the ongoing discussion on the implemetation of media literacy related contents into the education system. It introduces “Aturuxo Films”, an educational project developed within a secondary school curriculum which may be used as a reference point by other learning centres. “Aturuxo Films” has been recognised,amongst others, by the Spanish Ministry of Education, Culture and Sports, which awarded it their Media Literacy Prize in 2014.